OPTIMALISASI PERAN SERTA ULAMA DALAM DERADIKALISASI AGAMA - Hidayat, Thaufiq (JURNAL AL-AQIDAH, 2020)
Various acts of radicalism, which brought several disadvantages and anxieties to Indonesia's peace, have captured the attention of various circles. The act of radicalism that follows violence, threats and even murder becomes a separate motive that contributes to the problem of religious affairs, especially Islam. So far a number radical actions has been carried out by certain Muslims and this has been falsely taken to label Islam as a violent religion. Therefore, it is necessary to held deradicalization programs aimed particularly at religious leaders among society. This act counts as the antithesis of violent radicalism.This study aims to illustrate the steps and actions that must be taken  by scholars to alleviate the problem of radicalism. This study used description method. The deradicalization programs begin with the socialization of the negative effects of radicalism held by the government agency for countering terrorism (BNPT) to religious leaders, then the leaders preach it through various media.